The secret policeman's ball USA [videorecording (DVD)] : at Radio City Music Hall - Armisen, Fred, 1966-; Berry, Matt, 1974-; Brand, Russell, 1975-; Carr, Jimmy, 1972-; Cross, David, 1964-; Dratch, Rachel; Hader, Bill, 1978-; Izzard, Eddie; Jones, Rashida; Meyers, Seth, 1973-; O'Dowd, Chris, 1980-; Odenkirk, Bob, 1962-; et al. (Eagle Rock Entertainment, 2013)
In celebration of the fiftieth anniversary of Amnesty International, the Secret Policeman's Ball was staged in the USA for the first time at New York's famous Radio City Music Hall. With a history dating back to 1979, the Secret Policeman₂s Ball has always gathered the best comedy and musical talent to use wit and humor to raise both funds and awareness for the vital work that Amnesty International does to prick the conscience of governments around the world.